UNPACKING MULTILINGUAL INDONESIAN ISLAMIC HIGHER EDUCATION STUDENTS’ ATTITUDES TOWARDS ENGLISH AND ITS PROMISES - Al Umami, Habiba; Irham, Irham (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
Issues regarding attitudes and perceptions about English and its cultural politics have been widely and significantly reported in literature. As an international language, English signifies multiple and complex benefits and challenges. This paper aims to extend the discussion by interrogating students’ attitudes and unpack their views towards promises of English in Indonesian Islamic higher education (HE) settings. Participants in this study were undergraduate English Literature students who had engaged with the introductory principles of (Critical) Applied Linguistics (CPL). Data was collected through questionnaires (with closed and open-ended questions) from 58 participants, 19 males and 39 females, and semi-structured interviews with four students. The findings elucidated different views on varieties of English as students showed a quite moderate view of varieties of English from non-inner circle countries instead of treating them as something deficient. Dependency on native speakers’ English variety, however, seems to be negotiated in that the participants view intelligibility as more important in communication than, for instance, correctness. Moreover, students in the present study view speaking English with a local accent as something acceptable. Although not absolutely certain, they still presume that having competence in English can offer better hope in their future.